WATER RESOURCES CONSERVATION TO DRIVE ACHIEVEMENT OF SDGs IN SULI COUNTRY, MALUKU PROVINCE - Sitanala, Merlin Renny; Loppies, Ronny; Mardiatmoko, Gun; Parera, Lydia (LPPM Univ. Ibn Khaldun Bogor, 2023)
Suli Village, Salahutu Sub District, Central Maluku Districts is one of the coastal villages located in the east and directly opposite Baguala Bay, Ambon Island. As a Coastal Village, Suli has various potentials for biological natural resources. This existing potential must be managed by taking into account the conservation aspects, namely, protection, preservation, and utilization, to remain sustainable. The problems that arise in Suli Village include the lack of sensitivity among the community to be able to manage the environment properly. If left unchecked, natural resources which are the potential for development will be damaged and cause other problems in society. This is a challenge in the management of natural resources and existing ecosystems because they must maintain a balance between meeting human needs and the sustainability of their use to support life in development. To realize sustainable development, one of the efforts that can be done is to implement conservation activities as mandated in Constitution Number 5 of 1990. One way to do this is to carry out community service activities. This activity aims to conserve natural resources and the biodiversity contain while at the same time encouraging the achievement of sustainable development goals starting from the smallest community groups. The activities carried out are socializing the importance of living natural resources and their conservation efforts, environmental problems due to waste, and encouraging environmental conservation activities by becoming a customer of a waste bank. Finally, this service activity also indirectly contributes to the achievement of several goals and targets in the SDGs. Among the goals achieved were the environmental pillars, especially Goal 13 (handling climate change) and Goal 15 (terrestrial ecosystems).